2022
DOI: 10.7759/cureus.28367
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin Ameliorates Progression From Prediabetes to Diabetes and Improves Hepatic Lipid Metabolism: A Systematic Review

Abstract: Diabetes mellitus (DM) and hepatic steatosis are two of the most common metabolic syndromes that affect the health of people globally. Empagliflozin (EMPA) is a promising drug of choice for the diabetic population. Recent studies have shown its beneficial effects not only on diabetic patients but also on patients suffering from cardiac, hepatic, neurological, or pancreatic anomalies. In this paper, we systematically searched electronic databases to compile literature that focuses on EMPA’s effect on the predia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…A recent systematic review has also reported potential benefits of empagliflozin, a sodium–glucose cotransporter 2 (SGLT2) inhibitor with beneficial effects on T2D, heart failure and chronic kidney disease in individuals with NAFLD, improving hepatic triglycerides, decreasing visceral fat and reducing inflammatory markers and insulin resistance. [ 44 ]…”
Section: Management Of Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review has also reported potential benefits of empagliflozin, a sodium–glucose cotransporter 2 (SGLT2) inhibitor with beneficial effects on T2D, heart failure and chronic kidney disease in individuals with NAFLD, improving hepatic triglycerides, decreasing visceral fat and reducing inflammatory markers and insulin resistance. [ 44 ]…”
Section: Management Of Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…43 A recent systematic review has also reported potential benefits of empagliflozin, a sodium-glucose cotransporter 2 (SGLT2) inhibitor with beneficial effects on T2D, heart failure and chronic kidney disease in individuals with NAFLD, improving hepatic triglycerides, decreasing visceral fat and reducing inflammatory markers and insulin resistance. 44 Glucagon-like peptide-1 (GLP-1) analogues have a multitarget beneficial action in individuals with T2D, lowering plasma glucose, reducing liver steatosis and inflammation, improving cardiac function and protecting against kidney dysfunction. 45 Large retrospective studies on individuals with T2D and small Phase II RCTs in individuals with NAFLD and obesity treated with the GLP-1 analogue liraglutide showed significant dosedependent increases in insulin sensitivity, decreases in liver enzymes and advanced liver fibrosis, and amelioration of advanced liver fibrosis.…”
Section: Pharmacological Managementmentioning
confidence: 99%
“…Perakakis N. та співавтори (2021) вагою без ЦД, щодо зниження ознак ІР [115]. Таким чином, з'ясовано, що прийом ЕМПА в осіб з переддіабетом попереджає розвиток явного ЦД і покращує метаболізм ліпідів у печінці [116]. Треба зазначити, що безперервно збільшується кількість наукових праць щодо порівняння позитивних результатів лікування на зменшення чи утримання маси тіла у пацієнтів з ЦД 2-го типу при комбінації інсулінотерапії із іНЗКТГ2 та / чи іДПП-4 або арГПП-1, але у більшості із них не вивчалися прямі / непрямі ефекти на рівні печінки в осіб із МАЖХП.…”
Section: міжнародні настанови щодо медикаментозної терапії мажхпunclassified